A Literature Review on Internet of Medical Things - Shalini Sachdeva; Rajesh Sachdeva (International Journal of Wireless Security and Networks, 2025)
Artificial Intelligence (AI) is transforming healthcare by improving diagnostics, treatment planning, and patient management through data-driven insights and automation. The Internet of Medical Things (IoMT) represents a significant shift in modern healthcare, enabling real-time patient monitoring, data-driven decision-making, and enhanced medical outcomes. This literature review explores the architecture of IoMT, including perception layer, network layer, transport layer and application layer. It also thoroughly explores key challenges like ensuring data security, meeting regulatory requirements, and achieving seamless system interoperability. By analyzing recent studies and emerging trends, this review provides a comprehensive understanding of IoMT’s role in transforming healthcare delivery. It examines key technologies, including wearable sensors, remote monitoring systems, and AI-driven analytics, while also addressing critical concerns such as cybersecurity, interoperability, and data privacy. Moreover, this study emphasizes recent research on how the Internet of Medical Things (IoMT) influences patient health outcomes, enhances healthcare efficiency, and contributes to lowering costs.
Keywords: Confidentiality; IoMT; Wearable devices; artificial intelligence; integrity; security